Adolessente selfmoord en selfmoordgedrag : 'n pastoraal narratiewe beskouing (Afrikaans) - Muller, Julian C. (University of Pretoria, 2013)
Thesis (PhD (Practical Theology: Pastoral Family Therapy))--University of Pretoria, 2006.